Economic growth in ireland in 1980–2014. A threshold cointegration approach - Boehlke, Jerzy; Fałdziński, Marcin; Gałecki, Maciej; Osińska, Magdalena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The purpose of this paper is to identify the determinants of both the Gross National Product (GNP) growth in Ireland in the long term and the fluctuations around it in the short term using the Threshold Error Correction Model (TECM). The GNP aggregate has been selected as a measure of economic growth because it allows to omit the influence of international companies located in Ireland on the global production level. A TECM approach has been selected for analysis as it is an appropriate tool for the effective modeling of different regimes of growth around the long run which is assumed to be stable. The time series (in levels and in logs) exhibited both non-stationarity and structural breaks. It was possible to find out the determinants of growth in the long as well as short run and the threshold variables that extracted the period of intense economic growth. The best empirical models were obtained with the following thresholds: the GDP deflator and the net exports. The results have been a subject of validation for their robustness.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 157-188
Keywords: intense economic growth; Ireland; threshold cointegration; TECM; validation